Transcriptional inhibition of the Catalase gene in phosphine-induced oxidative stress in Drosophila melanogaster. - Liu, T.; Li, L.; Zhang, F.; Wang, Y. (Pesticide Biochemistry and Physiology, 2015)
Phosphine (PH3) is a toxic substance to pest insects and is therefore commonly used in pest control. The oxidative damage induced by PH3 is considered to be one of the primary mechanisms of its toxicity in pest insects; however, the precise mode of PH3 action in this process is still unclear. In this study, we evaluated the responses of several oxidative biomarkers and two of the main antioxidant enzymes, catalase (CAT) and superoxide dismutase (SOD), after fumigation treatment with PH3 in Drosophila melanogaster as a model system. The results showed that larvae exposed to sub-lethal levels of PH3 (0.028?mg/L) exhibited lower aerobic respiration rates and higher levels of hydrogen peroxide (H2O2) and lipid peroxidation (LPO). Furthermore, unlike SOD, the activity and expression of CAT and its encoding gene were downregulated by PH3 in a time- and dose-dependent manner. Finally, the responses of six potential transcription factors of PH3 were determined by real-time polymerase chain reaction to explore the regulation mechanism of DmCAT by PH3. There were no significant effects of PH3 on three nuclear factor-kappa B homologs (DORSAL, DIF, and RELISH) or two activator protein-1 genes (JUN and FOS), while dramatic inhibition of DNA replication-related element factor (DREF) expression was observed after fumigation with PH3, suggesting that PH3 could inhibit the expression of DmCAT via the DRE/DREF system. These results confirmed that PH3 induces oxidative stress and targets CAT by downregulating its encoding gene in Drosophila. Our results provide new insight into the signal transduction mechanism between PH3 and its target genes.